2021
DOI: 10.1063/5.0049717
|View full text |Cite
|
Sign up to set email alerts
|

Bandgap tunability of surface acoustic waves in a two-dimensional magneto-electro-elastic phononic crystal

Abstract: The propagation of surface acoustic waves in two types of tunable magneto-electro-elastic phononic crystal structures is investigated, for which Terfenol-D rods are vertically deposited on the piezoelectric substrate or embedded in the piezoelectric substrate. The bandgaps of the phononic crystal structures are analyzed by using the finite element method considering the nonlinear physical characteristics of Terfenol-D under a magnetic field and compressive pre-stress. Furthermore, through a detailed discussion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The band structure of PnCs can be actively tuned by modifying the elastic properties of the constituent materials via the application of external stimuli. In particular, numerous studies have revealed significant variations in the band structure of PnCs composed of magnetostrictive materials when exposed to a magnetic field [24][25][26][27][28][29][30]. Here, we investigate the integration of accurately designed PnC structures into SAW magnetic field sensors for advancements in sensitivity and overall sensor performance, holding promise for unlocking novel applications in industries where accurate and efficient magnetic field detection is of paramount importance.…”
Section: Introductionmentioning
confidence: 99%
“…The band structure of PnCs can be actively tuned by modifying the elastic properties of the constituent materials via the application of external stimuli. In particular, numerous studies have revealed significant variations in the band structure of PnCs composed of magnetostrictive materials when exposed to a magnetic field [24][25][26][27][28][29][30]. Here, we investigate the integration of accurately designed PnC structures into SAW magnetic field sensors for advancements in sensitivity and overall sensor performance, holding promise for unlocking novel applications in industries where accurate and efficient magnetic field detection is of paramount importance.…”
Section: Introductionmentioning
confidence: 99%
“…This feature promotes the wide application of the MEE in many fields of science and engineering, e.g., sensors [11], smart devices [12] and nondestructive evaluation [13], which are closely related to the knowledge of wave propagation. Various analytical and numerical techniques related to wave propagation in MEE structures were developed by numerous scholars [14][15][16][17][18]. However, few studies have focused on MEE piezoelectric phononic crystals.…”
Section: Introductionmentioning
confidence: 99%